Современный статус горихвостки-чернушки Phoenicurus ochruros (S.G.Gmelin) в Крыму - Цвелых, А.Н.; Бескаравайный, М.М. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2007)
The Black Redstart was known by now as a migrating and rare irregular wintering bird of the Crimea. To-date the Black Redstart is a migratory, breeding and regular wintering bird in the Crimea. At present the Black Redstart breeds in some populated areas of the Crimean peninsula. The southern border of the species breeding range extends up to the line Saky-Bakhchisarai district - Simferopol - Kerch Peninsula.